Project Based Learning: Model Pembelajaran untuk Meningkatkan Minat Belajar Tematik - Maya, Maya Agustina; Pipin, Tengku Hafinda; Wildatul Fajrina (azkiya, 2024)
This quantitative study aims to measure the inscrease in interest Thematic learning for MIN 7 Aceh Barat students using the model Project based learning learning. The research population is fourth grade students, IV, V and VI MIN 7 Aceh Barat and research samples are all grade IV students of MIN 7 Aceh. Data is collected using a questionnaire. Data analysis using simple frequency formula. The results showed that interest in learning students experienced an increase after the application of the Project based learning. The results of the student learning interest questionnaire conducted before the implementation of the project-based learning model showed that only one student was included in the "very high" category with a percentage of 6.6%, one student was included in the "high" category with a percentage of 6.6%, three students are included in the "sufficient" category with a percentage of 20%, ten students are included in the "less" category with a percentage of 66.8% and no students are in the "very poor" category. Meanwhile, the results of the student learning interest questionnaire conducted after the application of the project-based learning model showed that twelve students were included in the "very high" category with a percentage of 80%, three students were included in the "high" category with a percentage of 20%, and no students which is included in the category of "sufficient and very less" with a percentage of 0%.